Medicinal plants for traditional use in the south of Pará: an ethnobotanical study (Research, Society and Development, 2021)
Plants are an integral part of the culture of civilization, used as a food source or therapeutic purpose. Over time, the healing properties of vegetables were increasingly discovered and used. A cultural and valuable knowledge passed from generation to generation. However, in Brazil, research that assesses the degree of use of plants as medicines and their inclusion in popular culture are scarce, although there is a great tradition of their use in several biomes. In view of this, this research analyzed, through a questionnaire, which species of medicinal plants are most used in local traditional medicine and what their therapeutic purpose is. Qualitative exploratory/descriptive research was carried out with the inhabitants of the urban area of the city of Redenção located in the southern region of Pará, where interviews were conducted, using a questionnaire as a research instrument. It was found that respondents, in general, claim to make use of medicinal species and that most do so correctly. It was also observed that the main form of knowledge transmission is through the family. In this research, it was evident that the plants most used by the residents of this city are Lemongrass, Boldo-do-Chile or Boldo-Verdadeiro, Lemongrass, Mint and Matruz or Erva de Santa Maria, the leaves are the most used part and the tea as the main means of preparation.